Penanganan, Pengolahah, dan Pengawasan Pangan (Tanaman, Ikan dan Ternak) - Adriani Adriani (xxxx-xxxx, 2023)
Adriani A. 2022. Food handling, processing and control (plants, fish and livestock). In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang  27 Oktober 2022. pp. 18-26. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The purpose of handling, processing and controlling foodstuffs is to ensure their availability for the people of Indonesia. These foodstuffs must be in a healthy, safe and sustainable condition. However, in the development of food supply from plants, livestock and fish, there are global challenges. The global challenges of food supply are climate change which is uncertain, arable land is getting limited, clean water is getting limited and the population is increasing. Of course this is a challenge in the provision of food in the future. One of them is by increasing productivity, sustainability and quality. On the other hand, food handlers must pay attention to quality and quantity to consumers. Physical, chemical and biological treatment of food ingredients needs serious attention from raw materials, processing, transportation and storage to produce quality food. In accordance with the 5.0 industrial revolution, the availability of quality food is a priority so that the quality of human life increases, is safe and comfortable.